LS-LEACH: A New Secure and Energy Efficient Routing Protocol for Wireless Sensor Networks - Alshowkan, Muneer; Elleithy, Khaled; Alhassan, Hussain (2013 IEEE/ACM 17th International Symposium on Distributed Simulation and Real Time Applications, 2013)
Wireless sensor networks are facing many challenges such as the limited resource in processing power, storage and energy. The limited energy resource is one of the main challenges facing the security in such networks. This paper aims to improve the current security mechanisms in wireless sensor networks as well as reducing power consumption. LEACH protocol provides an energy routing protocol. However, it doesn't cover the security problems. Alternatively, this paper aims to provide an improved secure and more energy efficient routing protocol called LS-LEACH (Lightweight Secure LEACH). Authentication algorithm is integrated to assure data integrity, authenticity and availability. Furthermore, this paper shows the improvement over LEACH protocol that makes it secure and how to make it more energy efficient to reduce the effect of the overhead energy consumption from the added security measures.